Achieving Sustainable Development Goal 6 Electrochemical-Based Solution for Treating Groundwater Polluted by Fuel Station - da Silva, Júlio César Oliveira; Solano, Aline Maria Sales; Barbosa Segundo, Inalmar D.; dos Santos, Elisama Vieira [UNESP]; Martínez-Huitle, Carlos A. [UNESP]; da Silva, Djalma Ribeiro (MDPI, 2022)
Oil leakage occurs at fuel service stations due to improper storage, which pollutes soil and, subsequently, can reach the groundwater. Many compounds of petroleum-derived fuels pose hazards to aquatic systems, and so must be treated to guarantee clean and safe consumption, which is a right proposed by the United Nations in their Sustainable Development Goal 6 (SDG 6: Clean Water and Sanitation). In this study, contaminated groundwater with emerging pollutants by petroleum-derived fuel was electrochemically treated in constantly mixed 0.5 L samples using three different anodes: Ni/BDD, Ti/Pt, Ti/RuO2. Parameters were investigated according to chemical oxygen demand (COD), energy consumption analysis, by applying different electrodes, current densities (j), time, and the use of Na2SO4 as an electrolyte. Despite a similar COD decrease, better degradation was achieved after 240 min of electrochemical treatment at Ti/RuO2 system (almost 70%) by applying 30 mA cm−2, even without electrolyte. Furthermore, energy consumption was lower with the RuO2 anode, and greater when 0.5 M of Na2SO4 was added; while the order, when compared with the other electrocatalytic materials, was Ti/RuO2 > Ti/Pt > Ni/BDD. Thereafter, aiming to verify the viability of treatment at a large scale, a pilot flow plant with a capacity of 5 L was used, with a double-sided Ti/RuO2 as the anode, and two stainless steel cathodes. The optimal conditions for the effective treatment of the polluted water were a j of 30 mA cm−2, and 0.5 M of Na2SO4, resulting in 68% degradation after 300 min, with almost complete removal of BTEX compounds (benzene, toluene, ethyl-benzene, and xylene, which are found in emerging pollutants) from the water and other toxic compounds. These significant results proved that the technology used here could be an effective SDG 6 electrochemical-based solution for the treatment of groundwater, seeking to improve the quality of water, removing contaminants, and focusing on Brazilian environmental legislations and, consequently, converting pollutants into effluent that can be returned to the water cycle.
Keywords: anodic oxidation; BTEX; electrochemical oxidation; groundwater pollution; sustainable development goals